Species-specific gating of gametangial dehiscence as a temporal reproductive isolating mechanism in Coelomomyces - Federici, Brian A. (1983)
Hybridzygotes of Coelomomyces dodgei and Coelomomyces punctatus can be produced in the laboratory by making reciprocal crosses of their gametes. Although the F(1) hybrid sporophyte is viable, the F(1) gametophyte is inviable. Gametangial dehiscence (gamete release) in both species is relatively synchronous and follows a photoperiod-dependent diel periodicity, but even in populations grown under identical conditions, the gametes of each species are released during significantly different time frames. When the fungi are reared on an 8/16-hr dark/light regime, the gametes of C. punctatus are released during hours 7-11, whereas those of C. dodgei are released during hours 16-19. These results demonstrate that gametangial dehiscence is gated and, furthermore, indicate that this gating serves as a temporal reproductive isolating mechanism for these species of Coelomomyces. Additional preliminary studies with C. dodgei demonstrate that gametogenesis and gametangial dehiscence are photoperiod-dependent functions triggered by the onset of the dark period during the last day of gametophyte development, a dark period as short as 2 hr being sufficient to stimulate gametogenesis and gametangial dehiscence.